Analysis of Community Participation in the 2020 Medan Mayor Election During the Covid-19 Pandemic - Nora Yunita; R. Hamdani Harahap; Muryanto Amin (Universitas Medan Area, 2023)
The purpose of this study was to analyze community participation and the factors that led to the non-achievement of the national target in the 2020 Medan City Regional Head election. The method used is qualitative-descriptive research, namely by presenting the facts found in a comprehensive manner through in-depth analysis. While the data analysis technique consists of data reduction, data presentation and conclusion drawing. The results of the research obtained are that in the 2020 Medan Mayor election, the number of community participation increased and increased compared to previous years, but still the national target for political participation was not achieved. The popularity of candidates is an important aspect of increasing public participation in the 2020 Medan elections. The existence of candidates seems to have a curious effect on the people of Medan City. In addition, the results of the study also concluded that the factors that caused the national target for the 2020 regional elections in Medan were not achieved, namely the ambiguity of government policies. On the one hand, the Government wants Covid-19 to be completed immediately with various policies such as social distancing and avoiding crowds, but it is still like forcing the 2020 Regional Head Election which is one of the sources of crowds even though there are aspects of implementing health protocols.